Health education program regarding rabies knowledge for households in rural areas, assiut governorate, Egypt - Ragab Khalaf, Fatmaa; Abdelrahim Khalaf, Shimaa (International Journal of Nursing Research, 2023)
Rabies is a viral and vaccine-preventable zoonotic disease that occurs throughout the world; it is almost always fatal. Aim: was to assess the effect of a health education program on rabies knowledge for households in rural areas in Assiut Governorate. Materials and method: Cross-sectional quasi-experimental with one group pre/posttest research design; interview questionnaire used for data collection it was structured into two parts: Part (1): It included households' socio-demographic characteristics such as: age, sex, level of education, religion, occupation, family income and assessment of the social class according to Abdeltwab, 2010 and Part (2): It included questions regarding knowledge about rabies such as definition of rabies, modes of transmission of rabies, animals can transmit rabies….etc. The total sample size was 436 was interviewed in the randomly selected three villages affiliated to Assiut Governorate. Households were selected by systematic random sampling technique. Results: The present study revealed that36.2% of households their ages were 40-50 years, more than two-thirds of them were female and 42.2% of them had secondary education and less than half of the 48.2% were falling in the middle-level social class.94.5% households were had a poor score of knowledge in the pretest, while 66.1% were had a good score of knowledge in the posttest. Also, there were significant statistical differences in the pretest between the total score of knowledge and households' age, sex, educational level, occupation and social class. Conclusion: There was an improvement of the total score of knowledge regarding rabies among the households after application of the educational program.